Cost-to-Revenue Dynamics of Indonesia’s National Health-Insurance (BPJS Kesehatan) Services: Evidence from a Government Hospital Case Study - Martadinata, I Putu Hendra; Musmini, Lucy Sri; Prayudi, Made Aristia (E-Jurnal Akuntansi; Vol 35 No 5 (2025), 2025)
This study employs the cost-recovery rate (CRR) to evaluate the profitability of services delivered to National Health Insurance (BPJS Kesehatan) patients at the Regional General Hospital of Buleleng Regency. The hospital was selected for its comprehensive BPJS Kesehatan coverage, robust financial records, and logistical accessibility. Adopting a quantitative descriptive design, we juxtapose case-level revenues against corresponding costs to trace profitability patterns across key diagnoses. The analysis reveals positive CRR values—indicating financial surpluses—for stroke, acute diarrhoea, diabetes mellitus, and dengue haemorrhagic fever, yet shows a deficit for heart-failure management. These results provide an empirical basis for hospital administrators and policy-makers to refine reimbursement tariffs and optimise resource allocation in the treatment of BPJS Kesehatan patients. Keywords: Hospital Profitability; BPJS Kesehatan; Cost Recovery Rate.